A Review on Child Friendly Neighborhood, Case Study: Hewareberize Neighborhood, Sulaymaniyah, Northern Iraq - Omer, Berivan Aso (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
Children experience childhood in urban conditions progressively and more than one billion kids nowadays live in cities and towns. Cities and neighborhoods have to be safe and livable for children, because children‘s surrounding environment can significantly affect their entire lives. The planning and designing of projects related to children in cities and neighborhoods should be done for children and with children, because participation of children and using their ideas are the first step toward successful projects for all. Children‘s requirements in cities are the same as an adult‘s; all people want to have safe, secure, healthy life. So it is clear that a city good for children, is a city good for all. Every child has the rights to be protective and walk around their environment safely and experience new things. The Convention on the Rights of the Child embodies the most comprehensive explanation of the rights of children. The embodiment of the Convention of the rights of the Child at local level is the definition of a Child Friendly Cities (CFC). The aim of this study is to analyze and evaluate Hewareberize neighborhood in Sulaymaniyah in Northern-Iraq with principles of Child Friendly Cities, in order to determine existing situations and according to the findings, provide further recommendations for its improvements. The study emphasized the view and opinions of children as participants, and suggested that children must be central in the process of research. For reaching the aim a mixed methodology has been used as qualitative and quantitative method. Qualitative data has been collected through the cognitive map, the interview and observation; and quantitative data has been gathered by physical analysis and documentation and also observation. Twenty children aged between 6 to 12 years inside the Hewareberize neighborhood, have been participated in this study in doing the interview and the drawings which is the most effective way to understand children‘s feelings and requirements. This study recognizes the methods that can be used for analyzing and evaluating a community or neighborhood to determine a child-friendliness of that area. It has been mentioned that participation of children in these type of research is the most required to get more effective finding and results. Bases on the findings, the evaluation of the neighborhood have been done, with the principles of Child Friendly Cities. Then, several recommendations have been mentioned to make the neighborhood more children friendly.

ÖZ: Çocuklar kentsel koşullarda çocukluğunu aşamalı olarak yaşıyor ve günümüzde bir milyardan fazla çocuk şehirlerde ve kasabalarda yaşıyor. Şehirler ve mahalleler çocuklar için güvenli ve yaşanabilir olmalıdır, çünkü çocukların çevresindeki çevre tüm yaşamlarını önemli ölçüde etkileyebilir. Şehirlerde ve mahallelerde çocuklarla ilgili projelerin planlanması ve tasarlanması çocuklar için ve çocuklarla birlikte yapılmalıdır çünkü çocukların katılımı ve fikirlerini kullanmak herkes için başarılı projelerin ilk adımıdır. Şehirlerde çocukların gereksinimleri bir yetişkininki ile aynıdır; tüm insanlar güvenli, emniyetli ve sağlıklı bir yaşam sürmek ister. Dolayısıyla, çocuklar için iyi bir şehrin, herkes için iyi bir şehir olduğu açıktır. Her çocuğun koruyucu olma, çevrede güvenli bir şekilde dolaşma ve yeni şeyler deneyimleme hakları vardır. Çocuk Hakları Sözleşmesi, çocuk haklarının en kapsamlı açıklamasını içermektedir. Yerel düzeyde Çocuk Hakları Sözleşmesinin somutlaşmış hali, Çocuk Dostu Şehirler (ÇDŞ) tanımıdır. Bu çalışmanın amacı, Kuzey Irak'ta Süleymaniye'deki Hewareberize mahallesini Çocuk Dostu Şehirler ilkeleri ile analiz etmek ve değerlendirmek, mevcut durumları belirlemek ve bulgulara göre iyileştirmeleri için ilave öneriler sunmaktır. Çalışma, katılımcılar olarak çocukların görüşlerini ve fikirlerini vurguladı ve çocukların araştırma sürecinde merkezi olması gerektiğini öne sürdü. Amaca ulaşmak için nitel ve nicel yöntem olarak karma bir metodoloji kullanılmıştır. Bilişsel harita, görüşme ve gözlem yoluyla nitel veriler toplanmıştır; ve nicel veriler fiziksel analiz ve dokümantasyon ve ayrıca gözlem yoluyla toplanmıştır. Hewareberize mahallesinde yaşları 6-12 arasında değişen yirmi çocuk, çocukların duygu ve gereksinimlerini anlamanın en etkili yolu olan röportaj ve çizimlerin yapılmasında bu çalışmaya katılmıştır. Bu çalışma, o bölgenin çocuk dostu olup olmadığını belirlemek için bir topluluk veya mahalleyi analiz etmek ve değerlendirmek için kullanılabilecek yöntemleri tanımaktadır. Çocukların bu tür araştırmalara katılımının daha etkili bulgu ve sonuçlar elde etmek için en çok gerekli olduğu belirtilmiştir. Bulgulara dayanılarak mahallenin değerlendirilmesi Çocuk Dostu Şehirler ilkeleri ile yapılmıştır. Daha sonra mahalleyi daha çocuk dostu hale getirmek için birkaç tavsiyeden bahsedildi.
Master of Science in Urban Design. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2021. Supervisor: Prof. Dr. Mukaddes Polay.
Keywords: Architecture Department; Urban Design; Children--Development--Planning and Policy; Cities and towns--Planning--Children--Child Friendly; Child welfare--Sustainable development; Public spaces--Design; Community development, Urban--Sulaymaniyah (Northern Iraq); Children and the environment--Planning--Sulaymaniyah (Northern Iraq); Playgrounds--Children--Social aspects; Playgrounds--Children--Social aspects